PENGARUH STRATEGI KONFLIK KOGNITIF TERHADAP PENCAPAIAN KOMPETENSI PESERTA DIDIK DALAM PEMBELAJARAN FISIKA DI KELAS X SMAN 13 PADANG - Ladia Lestari; Amali Putra; Yurnetti Yurnetti (PILLAR OF PHYSICS EDUCATION, 2017)
Factors of the low students’ achievement of physics competence is the use of strategies that not appropriate to the material. The aim of this research was to determine the effect of applying the Cognitive Conflict Strategy Toward Students’ Competency Achievement in Physics Learning in Class X SMAN 13 Padang. The population is all Class X MIPA SMAN 13 Padang Academic Year 2016/2017, the sampling technique is a cluster random sampling. Quasi-Experimental Research is the type of this research with design Randomized Control Group Only Design. The competencies were measured in this research consist of the competence of knowledge, attitudes, and skills through , a written test, journal or observation sheets and performance assessment rubric. The three competencies were analyzed by using t-test.The obtaining of average values of two class sample showed experiment class is higher than control class of three competencies. Regression analysis showed a strong relationship between cognitive conflict strategy and knowledge competency. Correlation analysis of Product Moment showed 43.75% knowledge competency affected the applying cognitive conflict strategy. In conclusion, there is a significant impact the applying conflict strategy Toward Students’ Competency Achievement in Learning Physics in Class X SMAN 13 Padang on the 0,05 significan level